Edukasi Daur Ulang Minyak Goreng Bekas Menjadi Produk Aroma Terapi Ramah Lingkungan di Kelurahan Jelupang - Heri Wijayanto; Aliyah Aliyah; Moh. Ali Wisudawan Prakara (Jurnal Kabar Masyarakat, 2024)
Used oil is produced every day in every home, in its use, mothers are still not aware of the dangers that will be caused by the repeated use of used oil. The need for training to provide knowledge and be active in the environmental health of neighborhood neighborhoods in the Jelupang Village area of South Tangerang It is a must, considering the rainy season that has begun to be frequent, the disposal of used oil waste will clog the sewers in the Jelupang Village environment. With a qualitative approach in this Jelupang KKN, providing ideas for this training The results of the study show that this training program received a warm welcome from mothers who are members of the Jelupang Village Farmer Women's Group, who are waste bank activists in the village, and have been well coordinated, making it easier to conduct the training. They already have a stock of used cooking oil which is withdrawn and deposited every Wednesday per neighborhood in the village, the activists get new knowledge in creative use with a variety of models and sales results, with a variety of fragrances.